WAYS TO INCREASE THE COMPETITIVENESS OF NATIONAL PRODUCTION IN THE PROCESS OF FOREIGN TRADE LIBERALIZATION - Normuradovich, Rahimov Eshmurad (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article analyzes the main economic factor affecting the country's competitiveness - foreign trade. The main goal of the article is to explain the effect of trade liberalization and increasing the competitiveness of national production on increasing the competitiveness of the economy, strengthening the position of Uzbekistan in foreign trade, as well as the promotion of economic growth, the provision of further improvement of the welfare of the people, and the origin of international competitiveness, the connection between international trade and the competitiveness of the economy